Choice behavioral coping strategies in difficult situations - N A Sorokoumova; O V Golub (Peoples' Friendship University of Russia (RUDN University), 2010)
The article analyzes the behavioral strategies for coping with difficult situations, reveal the psychological characteristics that influence the choice of a coping strategy.